Exploration of Efficient Recognition Techniques for Sensitive Data Based on Feature Fusion - Hu, Jian; Zhang, Lina; Lu, Guangqian; Xu, Wenqian; Jiang, Yixin (Informatica, 2024)
At this stage, data has become essential and important information in people's daily life, and how to automate the identification and classification of sensitive attributes of structured datasets in the production environment, etc., has also become a key issue in data privacy protection. This paper proposes an efficient recognition technique for sensitive data based on feature fusion. The method can effectively improve the accuracy of sensitive data identification, realize the identification and classification of sensitive attributes, and take into account the correlation and association between attributes.